(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The study aimed to identify the level of psychological stress among a sample of postgraduate students at Latakia University in light of the earthquake that occurred on 6/2/2023. And aimed to identify the differences in the level of psychological stress among a sample members according to the following variables (gender, academic stage, and academic specialization). To achieve the objectives of this research, the Davidson stress scale was used after applying it to a survey sample from the original community, and ensuring its suitability for the research environment, it was applied to a sample of 547 students from Latakia University. The study also used the descriptive approach because it is appropriate for the nature of the research. The following results were reached: 1 – 34,6 % of the sample individuals have a low level of psychological stress , 50,8 % have a medium level, and 14,6 % have a high level. 2- There are no statistically significant differences between sample individuals in the level of psychological stress due to the gender variable. But they are differences between sample individuals in the level of psychological stress due to the variable of academic stage (master’s – doctorate), in favor of doctoral students, and the variable of academic specialization (theoretical colleges, applied colleges) in favor of students of theoretical colleges.